Highlights of the 2014 Ocean Sciences Meeting. Issue 26 (1st July 2014) - Sharp, Jonathan; Briscoe, Melbourne; Itsweire, Eric
<x xml:space="preserve">Abstract</x> The 2014 Ocean Sciences Meeting was the 17th biennial gathering since the inception of ocean sciences meetings in 1982. A joint venture of the Association for the Sciences of Limnology and Oceanography (ASLO), The Oceanography Society (TOS), and the Ocean Sciences section of AGU, the meeting was by far the largest ever: More than 5600 attendees made this meeting more than 30% larger than any previous one. Forty percent of attendees live outside the United States, hailing from 55 countries, showing the importance of this meeting as an international gathering of ocean scientists.